PENGEMBANGAN STRATEGI PEMASARAN DIGITAL UNTUK UMKM DI DESA BAROS KECAMATAN WARUNGGUNUNG, KABUPATEN LEBAK - Ni’mah, Ratu Sifa; Lestari, Dini Martinda; Nur, Silfi Purnama; Hidayat, Defa Lutfy; Rahman, Airini (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
This service activity aims to develop digital marketing strategies for MSMEs in Baros Village, Warunggunung District, Lebak Regency. The process begins with a preparation stage which includes identifying the needs of MSMEs through surveys and preparing training materials. Training covers the basics of digital marketing, use of social media, website creation, and search engine optimization (SEO) techniques. At the implementation stage, participants are given practical knowledge and immediately apply the strategies they have learned. The results of the activity showed an increase in participants' knowledge and skills, effective implementation of digital marketing strategies, as well as an increase in website traffic and product sales. Despite challenges such as limited resources, continuous monitoring and evaluation ensures the effectiveness of the strategies implemented. This program is expected to help Baros Village MSMEs utilize digital marketing to increase product competitiveness and make a positive contribution to the local economy